Influence of CReatine supplementation on mUScle mass and strength after stroke (ICaRUS Stroke Trial): study protocol for a randomized controlled trial - Souza, Juli Thomaz de [UNESP]; Minicucci, Marcos F. [UNESP]; Ferreira, Natália C. [UNESP]; Polegato, Bertha F. [UNESP]; Okoshi, Marina Politi [UNESP]; Modolo, Gabriel P. [UNESP]; Phillips, Bethan E.; Atherton, Philip J.; Smith, Kenneth; Wilkinson, Daniel; Gordon, Adam; Tanni, Suzana E. [UNESP]; et al. (Springer Nature, 2023)
Background: Stroke is a leading cause of mortality and disability, and its sequelae are associated with inadequate food intake which can lead to sarcopenia. The aim of this study is to verify the effectiveness of creatine supplementation on functional capacity, strength, and changes in muscle mass during hospitalization for stroke compared to usual care. An exploratory subanalysis will be performed to assess the inflammatory profiles of all participants, in addition to a follow-up 90 days after stroke, to verify functional capacity, muscle strength, mortality, and quality of life. Methods: Randomized, double-blind, unicenter, parallel-group trial including individuals with ischemic stroke in the acute phase. The duration of the trial for the individual subject will be approximately 90 days, and each subject will attend a maximum of three visits. Clinical, biochemical, anthropometric, body composition, muscle strength, functional capacity, degree of dependence, and quality of life assessments will be performed. Thirty participants will be divided into two groups: intervention (patients will intake one sachet containing 10g of creatine twice a day) and control (patients will intake one sachet containing 10g of placebo [maltodextrin] twice a day). Both groups will receive supplementation with powdered milk protein serum isolate to achieve the goal of 1.5g of protein/kg of body weight/day and daily physiotherapy according to the current rehabilitation guidelines for patients with stroke. Supplementation will be offered during the 7-day hospitalization. The primary outcomes will be functional capacity, strength, and changes in muscle mass after the intervention as assessed by the Modified Rankin Scale, Timed Up and Go test, handgrip strength, 30-s chair stand test, muscle ultrasonography, electrical bioimpedance, and identification of muscle degradation markers by D3-methylhistidine. Follow-up will be performed 90 days after stroke to verify functional capacity, muscle strength, mortality, and quality of life. Discussion: The older population has specific nutrient needs, especially for muscle mass and function maintenance. Considering that stroke is a potentially disabling event that can lead the affected individual to present with numerous sequelae, it is crucial to study the mechanisms of muscle mass loss and understand how adequate supplementation can help these patients to better recover. Trial registration: The Brazilian Clinical Trials Registry (ReBEC) RBR-9q7gg4. Registered on 21 January 2019.
Keywords: Creatine; Sarcopenia; Skeletal muscle; Stroke